Penatalaksanaan Hiperemesis Gravidarum - Ristiyana, Septi; Destri, Yuhelva; Safitri, Oktaria; Pitri, Intan Agutina (Jurnal Ilmu Kebidanan, 2024)
Background: Hyperemesis gravidarum is a condition characterized by excessive nausea and vomiting, weight loss and electrolyte balance disturbances, the mother looks thinner, reduced skin turgor, and sunken eyes. If pregnant women who experience this do not handle it properly it can cause other problems, namely increased stomach acid and can subsequently develop gastritis (Astuti, 2016). Methods: The type of case report used is a descriptive report with a case study approach (case review study). Case studies are carried out by examining a problem through a case consisting of a single unit. Results: From the results of research in Indonesia, it was found that pregnant women with hyperemesis gravidarum reached 14.8% of all pregnancies, while the incidence of hyperemesis gravidarum in Indonesia in 2016 was 1.5-3% of pregnant women, complaints of nausea and vomiting occurred in 60-80% primigravidas and 40-60% multigravidas. The feeling of nausea and vomiting is caused by increased levels of the hormone estrogen and the hormone Chorionic Gonadotropin (HCG) in serum (Ministry of Health RI, 2016). Conclusion: Performed on Mrs. R obtained biodata results, namely Mrs. R, 30 years old, G3P2A0, 13 weeks pregnant, with maternal complaints of nausea, vomiting more than 4 times a day, decreased appetite, dizziness and weakness.